L’appropriation par les habitants des dispositifs de végétalisation urbaine participative à Lyon : quelles inégalités socio-spatiales ? - Amélie Deschamps (Développement Durable et Territoires)
Since early 2000’s, the inhabitants of Lyon (France) are increasingly involved in city greening with community and street gardening. Public authorities support and supervise this involvement through charters and financial assistance. Yet, to put together an application in order to be allowed to make public space greener takes time and requires some administrative ease. Hence this paper examining the location of inhabitants’ initiatives regarding to socio-economic inequalities previously existing in the city. We argue that participatory urban greening generates environmental injustice in the city. The legal frame set by the municipality acts as a social filter, populations unfamiliar with its mechanics are set aside. It is only by the action of intermediary associative actors that they can engage in participatory urban greening with community gardening. However, street gardening remains a privileged leisure.